Sibling Gender Composition and Women's Wages - Angela Cools; Eleonora Patacchini (Institute of Labor Economics (IZA), 2017)
We examine the impact of sibling gender composition on women's adult earnings. Using data from Add Health, we find that women with any brothers earn roughly 10 percent less than women with no brothers in their late 20s and early 30s. This effect is primarily due to lower earnings within broadly defined education and occupation groups. We then explore mechanisms that may explain this result. We do not find strong evidence that differences in parental investment, cognitive ability, self-reported personality traits, or parental expectations drive our results. However, we find that more family-centered behavior (including family responsibilities, being in a committed relationship, and intention to have children) among those with brothers partially explains the result. We then confirm our results with data from the NLSY-CYA.
Keywords: J12; J13; J16; J31; 330; sibling sex composition; gender gap; gender roles; earnings